Transobturator suburethral tape procedure (TOT) in the treatment of female stress urinary incontinence. Our experience - Rosas Maccari, Miguel (2015)
Objectives: To analyze predisposing factors in stress urinary incontinence (USI). To value transobturator suburethral tape procedure efficacy and security (TOT) in female USI treatment. Design: Observational retrospective study. Setting: Gynecology and Obstetrics Service, Xarxa Sanitaria i Social de Santa Tecla. Hospital Vendrell. Red sanitaria publica. Tarragona. Cataluya. Espanya. Participants: Patients with USI diagnosis. Interventions: Sixty patients with USI diagnosis were treated between October 2006 and February 2010. Three types of mesh from different commercial stores (Aris, Gynecare and Monarc) were used. Placing technique in most patients was out–in with transobturator approach, with exception of Gynecare placed in–out. Main outcome measures: USI cure. Results: Median age was 56 years, most frequent history showed obesity in 50%, arterial hypertension 32% and hysterectomy 27%. Cure rate (defined as absolute absence of leak by history and clinical exam) was 83% at one month from surgery, 83% in one year, and 70% at follow-up over one year. Correction of other vaginal compartment defects was done in 12%. There was no complication during surgery. Hospitalization lasted 0,8 day. Post surgery complications were urinary retention in 10%, bladder tenesmus in 8%, de novo urgency in 8%, mesh extrusion in 2% and dyspareunia in 3%. Conclusions: Our results are comparable to those published in the literature. In our experience TOT represents a safe technique, very efficacious in time for USI treatment in patients with mobile urethra, and with few complications. Learning curve is short and it is possible to do it in ambulatory major surgery regime.